The Presentation Form of Sholawat Ya-lail to The Serang City People, Banten Province - Syamsul Rizal; Farhan Fahreza (Universitas Negeri Surabaya, 2023)
The problem discussed in this study is about the presentation of the art of sholawat Ya-lail in the community of Babakan Gelam Village, Cipocok Jaya District, Serang City, Banten Province. The purpose of this study was to describe the presentation of the art of sholawat Ya-lail in the Babakan Gelam Village, Cipocok Jaya District, Serang City community. The approach used in this research is descriptive qualitative. The object of research is the presentation of the art of sholawat Ya-lail, which includes the form of presentation and the meaning of the art. Collecting data by observation, interview, and documentation. The data analysis stages are data reduction, (2) data presentation, and conclusion.The results showed that the presentation of the art of sholawat Ya-lail in the community of Babakan Gelam Village, Cipocok Jaya District, Serang City, is the art of sound, because it uses seven games, namely (1) Balam Bayati, (2) Lalam Hijaz, (3) Lalam Ros, (4) Lagam Nahawand, (5) Lagam Shoba, (6) Lagamjiharkah, (7) Lagam Sikah.